DIVERSITY OF MACROSCOPIC FUNGI IN THE LOMBONGO TOURISM PARK AREA GORONTALO PROVINCE - Ani M. Hasan; Herinda Mardin; Dian Alfiani; Ledy Muthmainnah Y. Syahril; Nadia Fajri Panyilie; Riska Iman; Sindyawati Lasangole; Sri Fujiatun Mardjun (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2022)
Fungi are organisms that do not have chlorophyll and are heterotrophic. Fungi can be found everywhere, both in the tropics, subtropics, at the North Pole and Antarctica. Mushrooms have very diverse types. The area of Lombongo Tourism Park, Gorontalo Province has various types of mushrooms. The Lombongo Tourism Park area is an area under the foot of Tilong Kabila mountain in Bone Bolango Regency, Gorontalo Province. The purpose of this study was to identify the types of macroscopic fungi in the Lombongo Tourism Park area of Gorontalo Province. This research was conducted in October 2020 at the Lombongo Tourism Park using the Cruise Method. The tools and materials used are digital cameras, GPS, masks, plastic gloves and writing instruments. The results showed that in the area of Lombongo Tourism Park, Gorontalo Province, there were 32 types/species of macroscopic fungi belonging to the Basidiomycota and Ascomycota divisions. The Basidiomycota division consists of 2 classes, namely Agaricomycetes and Basidiomycetes while the Ascomycota division consists of 1 class, namely Pezizomycetes. In the area of Lombongo Tourism Park, Gorontalo Province as a whole there are 3 classes, 6 orders, 16 families, 24 genus and 32 species. Family Polyporaceae which are mostly found in the area of Lombongo Tourism Park, Gorontalo Province.